Analysis of reaction mixtures of perhydro-dibenzyltoluene using two-dimensional gas chromatography and single quadrupole gas chromatography - Modisha, Phillimon M.; Jordaan, Johan H. L.; Bösmann, Andreas; Wasserscheid, Peter; Bessarabov, Dmitri (International Journal of Hydrogen Energy, 2018)
Energy storage via liquid organic hydrogen carrier (LOHC) systems has gained significant attention in recent times. A dibenzyltoluene (DBT) based LOHC offers excellent properties which largely solve today's hydrogen storage challenges. Understanding the course of the dehydrogenation reaction is important for catalyst and process optimization. Therefore, reliable and exact methods to determine the degree of hydrogenation (doh) are important. We here present other possible techniques, namely: comprehensive two-dimensional gas chromatography coupled with time of flight mass spectrometry (2D-GC-TOF-MS) and single quadrupole-mass spectrometry gas chromatogram system (GC-SQ-MS). The 2D-GC-TOF-MS results indicate that isomer fractions lose three molecules of hydrogen, as follows: H18-DBT, H12-DBT, H6-DBT and H0-DBT, and the doh decreases with an increase in dehydrogenation temperature. 1H NMR and GC-SQ-MS were employed as additional analytical techniques. The GC-SQ-MS was also used to analyse decomposition products that result from thermal cracking of reaction mixture molecules.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Dehydrogenation; Dibenzyltoluene; Hydrogen storage; Liquid organic hydrogen carrier (LOHC); Time-of-flight mass spectrometry; Two-dimensional gas chromatography